THE RELATIONSHIP BETWEEN GENDER, STRESS AND JOB PERFORMANCE AMONG ACADEMIC STAFF IN TERTIARY INSTITUTIONS IN ANAMBRA STATE, NIGERIA - Sofoluwe, Abayomi Olumade; Akinsolu, Abiodun Olatoun; Ogbudinkpa, Ijeoma Charity (European Scientific Journal, ESJ, 2015)
This study investigated the relationship among gender, stress and academic job performance in tertiary institutions in Anambra State. The research design was descriptive survey of correlational type. Stratified random technique was used to select a total of 500 participants out of 1,200 target population from the four tertiary institutions in Anambra State of Nigeria. The data gathering instrument were Gender Stress Questionnaire (GSQ), Academic Staff Job Performance Questionnaire (ASJPQ), Academic Staff Stress Management Check List (ASSMCL) and Academic Staff Publication Proforma (ASPP). Five hypothesis generated were tested at .05 level of significance. The data were analyzed using Multiple Regression and Pearson Product Moment Correlation Coefficient Statistics. The findings revealed that gender and stress significantly influenced academic staff job performance in tertiary institutions in Anambra State. It was recommended that the workload of the lecturers should be reduced so as to achieve efficiency and effectiveness in their teaching career.